Treatment of Hidradenitis Suppurativa Evaluation Study (THESEUS): protocol for a prospective cohort study. Issue 4 (21st April 2022) - Bates, Janine; Stanton, Helen; Cannings-John, Rebecca; Thomas, Kim Suzanne; Leighton, Paul; Howells, Laura M; Rodrigues, Jeremy; Howes, Rachel; Collier, Fiona; Harris, Ceri; Gibbons, Angela; Thomas-Jones, Emma; et al.
Abstract : Background: Hidradenitis suppurativa (HS) is a chronic, painful, inflammatory skin disease with estimates of prevalence in the European population of 1%–2%. Despite being a relatively common condition, the evidence base for management of HS is limited. European and North American management guidelines rely on consensus for many aspects of treatment and within the UK variations in management of HS have been identified. The HS James Lind Alliance Priority Setting Partnership (PSP) published a top 10 list of future HS research priorities including both medical and surgical interventions. The aims of the THESEUS study are to inform the design of future HS randomised controlled trials (RCTs) and to understand how HS treatments are currently used. THESEUS incorporates several HS PSP research priorities, including investigation of oral and surgical treatments. Core outcome domains have been established by the HIdradenitis SuppuraTiva cORe outcomes set International Collaboration (HISTORIC) and THESEUS is designed to validate instruments to measure the domains. Methods and analysis: The THESEUS study is a prospective observational cohort study. Participants, adults with active HS of any severity, will be asked to select one of five HS treatment options that is appropriate for their HS care. Participants will be allocated to their chosen treatment intervention and followed for a period of up to 12 months. Outcomes will be assessed at 3-monthly intervals using HISTORIC core outcome instruments. Video recordings of the surgical and laser operations will provide informational and training videos for future trials. Nested mixed-methods studies will characterise the interventions in clinical practice, understand facilitators and barriers to recruitment into future HS RCTs and examine patients' and clinicians' perspectives on HS treatment choices. Trial registration number: ISRCTN69985145 .